2016
DOI: 10.1016/j.childyouth.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Case management for child protection services: A multi-level evaluation study

Abstract: This article presents an evaluation study of a case management method for child protection services, the Delta Method for Family Supervision, in terms of supervision order duration and occurrence and duration of out-ofhome placements. Additionally, case and case manager characteristics were examined. Data was collected about 224 cases, 58 case managers and 30 team managers of all 15 offices of the Child and Youth Protection Services in the Netherlands. In all cases the Delta Method was applied. Data were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
(41 reference statements)
2
17
0
Order By: Relevance
“…Parenting practices now regarded as (a type of) child maltreatment may have been acceptable parenting behavior in earlier years. On the other hand, child welfare professionals may have become more sensitive to (different types of) child maltreatment, as child welfare has increasingly professionalized over time (Busschers, Van Vugt, & Stams, 2016). These aspects may limit the accuracy in assessing child maltreatment in parents using official records, and may explain why we found an (almost) equal effect size for official records and self-report methods.…”
Section: Moderator Effectsmentioning
confidence: 85%
“…Parenting practices now regarded as (a type of) child maltreatment may have been acceptable parenting behavior in earlier years. On the other hand, child welfare professionals may have become more sensitive to (different types of) child maltreatment, as child welfare has increasingly professionalized over time (Busschers, Van Vugt, & Stams, 2016). These aspects may limit the accuracy in assessing child maltreatment in parents using official records, and may explain why we found an (almost) equal effect size for official records and self-report methods.…”
Section: Moderator Effectsmentioning
confidence: 85%
“…Although no specific contextual factors, structural elements or program components were found that significantly contributed to the overall effect of parent training programs, there are a number of common factors that all interventions need in order to be effective, regardless of the target group and the type of intervention. For example, programs should have a clear structure and a clear goal [64,65]. Furthermore, programs should be delivered as intended (i.e., according to the manual or protocol), as a higher level of program integrity is associated with larger significant effects of programs on various outcomes [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Going further back in time would substantially reduce the relevance of our study for the more recent developments in foster care, case management in child welfare, and society at large. For instance, many changes took place in the lives of families after 1990 (e.g., further decline of the extended family, higher divorce rates, non-traditional family arrangements, lower birth rates) in the Western world (OECD, 2011), while case management in child welfare gradually became an evidence-based practice (Busschers, Van Vugt, & Stams, 2016). We included studies on instability if they focused on breakdown (placement is ended unplanned and prematurely, before the goals were achieved), disruption (unplanned move from one foster family to another), or multiple foster care placements.…”
Section: Selection Of the Studiesmentioning
confidence: 99%